2022
DOI: 10.5009/gnl220025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Trial between I-SCAN-Optical Enhancement and Chromoendoscopy for Evaluating the Horizontal Margins of Gastric Epithelial Neoplasms

Abstract: Background/Aims: Endoscopic submucosal dissection is a widely used treatment for gastric epithelial neoplasms. Accurate delineation of the horizontal margins is necessary for the complete resection of gastric epithelial neoplasms. Recently, image-enhanced endoscopy has been used to evaluate horizontal margins of gastric epithelial neoplasms. The aim of this study was to investigate whether I-SCAN-optical enhancement (I-SCAN-OE) is superior to chromoendoscopy in evaluating the horizontal margin of gastric epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The I-SCAN method, developed by PENTAX (Tokyo, Japan), consists of various types of post-processing images to enhance the surface, contrast, and tone. In a comparison trial, i-SCAN showed similar results compared with dye CE (acetic acid and indigo carmine) to delineate the margins of gastric lesions [51].…”
Section: Virtual Chromoendoscopymentioning
confidence: 90%
“…The I-SCAN method, developed by PENTAX (Tokyo, Japan), consists of various types of post-processing images to enhance the surface, contrast, and tone. In a comparison trial, i-SCAN showed similar results compared with dye CE (acetic acid and indigo carmine) to delineate the margins of gastric lesions [51].…”
Section: Virtual Chromoendoscopymentioning
confidence: 90%
“…Several studies have found that i-Scan does not provide significant advantages in detecting gastric cancer lesions or determining their extent when compared with high-definition white light endoscopy or pigmented endoscopy. However, the use of i-Scan could largely reduce the need for unnecessary biopsies compared to WLE (with a mean number of biopsies per patient of 3.27 and 7.3, respectively) 79 , 80 .…”
Section: Endoscopy Screening For Early Gastric Cancermentioning
confidence: 99%
“…This is accomplished by linking the highest points of the hemoglobin absorption spectrum (at 415, 540, and 570 nm), resulting in the creation of a seamless spectrum of wavelengths, which is almost identical to the principle of NBI [ 24 ]. Although i-scan OE operates on a similar principle as NBI, a few studies have suggested new diagnostic criteria, which are different from those of NBI [ 25 , 26 , 27 , 28 ]. However, they are not commonly used by many endoscopists.…”
Section: Introductionmentioning
confidence: 99%